Challenges of feedback provision in the workplace: A qualitative study of emergency medicine residents and teachers. (2nd November 2017) - Chaou, Chung-Hsien; Monrouxe, Lynn V.; Chang, Li-Chun; Yu, Shiuan-Ruey; Ng, Chip-Jin; Lee, Ching-Hsing; Chang, Yu-Che
Abstract: Background: Feedback is an effective pedagogical tool in clinical teaching and learning, but is often perceived as unsatisfactory. Little is known about the effect of a busy clinical environment on feedback-giving and -seeking behaviors. This study aims to determine the perceptions and challenges of feedback provision in a busy clinical setting, exemplified by an emergency department (ED). Methods: A qualitative semi-structured interview study design was employed. Thirty-six participants (18 attending physicians, 18 residents) were purposively sampled from three EDs in northern Taiwan between August 2015 and July 2016. Interviews were recorded, transcribed, and analyzed thematically. Results: Three major themes were identified with illustrative quotes: (1) the balance between patient safety and providing feedback, (2) variability in feedback, and (3) influential factors, barriers and enablers. Conclusions: In real practice, clinical duties competed with the impulse to provide feedback. The variety and complexity of feedback extended beyond style and content. Clinical and contextual factors – some of which may be presented as barriers – influenced how, when and whether a teacher or learner decided to give or seek feedback.